Social Media Jealousy and Life Satisfaction in Romantic Relationships: Mediation Role of Communication Skills - Ayşen Kovan (Actualidades en Psicología, 2023)
Objective. The main aim of this study is to examine the mediation role of communication skills in the relationship between social media jealousy and life satisfaction in individuals with romantic relationships. Method. The sample group of the study consisted of a total of 445 individuals who have a romantic relationship, 228 females and 217 males aged from 18 to 31 in the period of emerging adulthood. The mean age of participants in the study was 23.49 (SD = 3.29). In order to gather data Social Media Jealousy Scale, Life Satisfaction Scale and Communication Skills Scale. Results. According to the findings of the study, social media jealousy negatively predicted life satisfaction. The main focus and other important finding of the study was that communication skills mediated the relationship between social media jealousy and life satisfaction. This study emphasises the mediating role of communication skills between social media jealousy and life satisfaction in individuals with romantic relationships and suggests that developing and strengthening communication skills. This study points to an important area in terms of understanding and improving the effects of social media interactions on emotional experience and life satisfaction.